Phenotype characterization of Staphylococcus species strains isolated from buffalo (Bubalus bubalis) milk - Oliveira, Andrea A. F.; Pinheiro, Jose W.; Mota, Rinaldo A.; Cunha, Maria L. R. S. [UNESP]; Lopes, Carlos A. M. [UNESP]; Rocha, Noeme S. [UNESP] (Sage Publications Inc, 2011)
The objective of the current study was to isolate and identify phenotypes of Staphylococcus spp. strains derived from buffalo (Bubalus bubalis) milk. A total of 548 milk samples from 137 buffalo were cultured in Columbia agar enriched with 5% defibrinated sheep blood. Determination of the capacity of Staphylococcus aureus to produce enterotoxins A-D and toxic shock syndrome toxin-1 (TSST-1) was achieved by reverse passive latex agglutination (RPLA). Antimicrobial sensitivity of S. aureus strains was evaluated using the disk diffusion technique, and beta-lactamase detection was achieved using the chromogenic test with paper discs impregnated with nitrocefin. From all the mammary quarters examined, 36 (10.8%) were positive for Staphylococcus spp., 83.3% were coagulase-negative staphylococcus (CNS), 11.1% were coagulase-positive staphylococcus (CPS), and 5.6% were of CPS+CNS positive. All isolates of S. aureus produced at least 1 toxin and 5 out of 6 isolates (83.0%) produced beta-lactamase. One hundred percent of S. aureus isolates were sensitive to methicillin and amoxicillin + clavulanic acid, and resistant to ampicillin, penicillin, and oxacillin. Analysis of the results obtained in the current study highlight the epidemiologic importance of buffalo milk regarding the production of enterotoxins and TSST-1 and the potential risk to public health.
Keywords: Antibiotics; Bubalus bubalis; buffalo; enterotoxin; milk